2010
DOI: 10.1016/j.socnet.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Does the online collection of ego-centered network data reduce data quality? An experimental comparison

Abstract: a b s t r a c tWe analyze whether differences in kind and quality of ego-centered network data are related to whether the data are collected online or offline. We report the results of two studies. In the first study respondents could choose between filling out ego-centered data through a web questionnaire and being probed about their network in a personalized interview. The second study used a design in which respondents were allocated at random to either online or offline data collection. Our results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…94-95). More specifically, item nonresponse to the name interpreter questions may become prevalent in the name generator procedure (Matzat and Snijders, 2010;Vehovar et al, 2008), especially when respondents become overwhelmed after enumerating a long list of names during the preceding generator. In addition, respondents may also be only willing to spend a very brief amount of time (i.e., minimal effort) to produce optimal responses to the demanding question, especially when answering questions closer to the end of the survey (Malhotra, 2008;Yan and Tourangeau, 2008), indicating a classic satisficing behavior that respondents were answering as fast as possible to complete the task.…”
Section: Demanding Cognitive Effort and Subsequent Satisficing Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…94-95). More specifically, item nonresponse to the name interpreter questions may become prevalent in the name generator procedure (Matzat and Snijders, 2010;Vehovar et al, 2008), especially when respondents become overwhelmed after enumerating a long list of names during the preceding generator. In addition, respondents may also be only willing to spend a very brief amount of time (i.e., minimal effort) to produce optimal responses to the demanding question, especially when answering questions closer to the end of the survey (Malhotra, 2008;Yan and Tourangeau, 2008), indicating a classic satisficing behavior that respondents were answering as fast as possible to complete the task.…”
Section: Demanding Cognitive Effort and Subsequent Satisficing Behaviorsmentioning
confidence: 99%
“…Consequently, the name generator tends to capture close confidants -a limited subset of personal network members (Marsden, 1987). In addition, some recent studies (Matzat and Snijders, 2010;Vehovar et al, 2008) have discovered that, not only were respondents likely engaged in satisficing behaviors Krosnick, 1991) when answering to the name generator procedure, but they were much more likely to provide inferior quality data or drop out in a self-administered Web survey than other survey modes in the presence of interviewers. Thus far, although a few techniques for delimiting comprehensive personal networks (e.g., Bidart and Charbonneau, 2011;Brewer and Garrett, 2001;Hlebec et al, 2006;Marin, 2004) and reducing the respondent burden (Marin and Hampton, 2007;McCarty et al, 2007) have been proposed, there is little work addressing the use of memory aids (e.g., Glasner and van der Vaart, 2009) that improve the recall accuracy for personal network data collection.…”
Section: Introductionmentioning
confidence: 99%
“…First, a portion of the phase 2 interview involved gathering egocentric network data which has traditionally been collected in person 19,20 and has been proven to be more successful than trying to obtain this data using online surveys. 21 Second, the phase 2 interview also included a series of gender-based violence exposure items. Research has shown that gender-based violence survivors may benefit from participating in research which directly asks about such exposures, with greater positive gains reported from respondents participating in interview-administered surveys versus written surveys.…”
mentioning
confidence: 99%
“…Given the time-consuming and demanding nature of eliciting network characteristics from respondents, a staff-administered questionnaire was deemed an appropriate mode of data collection. Interviewers not only motivate respondents to complete the survey, but they can also answer questions and provide procedural explanations when needed (Matzat & Snijders, 2010; Tourangeau, Rips, & Rasinski, 2000). …”
Section: Methodsmentioning
confidence: 99%